Trends and determinants of adolescent pregnancy: Results from Kenya demographic health surveys 2003-2014. - Mutea, Lilian; Were, Vincent; Ontiri, Susan; Michielsen, Kristien; Gichangi, Peter (BMC Women's Health, 2022)
Background: Adolescent pregnancy increases the risk of disability and death due to unsafe abortion, prolonged labour and delivery, and complications after birth. Availability of accurate data is important to guide decision-making related to adolescent sexual reproductive health (ASRH). This study analyses the trends in prevalence and factors associated with adolescent pregnancy in Kenya using data from three national Demographic Health Surveys (2003, 2008/2009, 2014).Methods: Our analysis focused on a subsample of data collected from women aged 20 to 24 years. A trend analysis was performed to establish a change in the rate of adolescent pregnancy in 2003, 2008/2009, and 2014 survey data points. Binary Logistic regression and pooled regression analysis were used to explore factors associated with adolescent pregnancy.Results: The percentage of women aged 20 to 24 years who reported their first pregnancy between ages 15 and 19 years was 42% in 2003 and 42.2% in 2009 but declined to 38.9% in 2014. Using regression analyses, we established that education status, marital status, religion and wealth quintile were associated with adolescent pregnancy. Trend analysis shows that there was an overall decreasing trend in adolescent pregnancy between 2003 and 2014.Conclusion: Although Kenya has made strides in reducing the prevalence of adolescent pregnancy in the last decade, much more needs to be done to further reduce the burden, which remains high.Definition: Adolescents: Although WHO defines the adolescence period as being 10-19 years, this paper focuses on the late adolescent period, 15-19 years, here in referred to as adolescents.